PF.03 Criteria For a Legitimate Life: Termination of Pregnancy For Non-Lethal Fetal Anomaly as an Acceptable Outcome For an Affected Pregnancy. (26th April 2013) - Crowe, L; Graham, RH; Robson, SC; Rankin, J
Abstract : Introduction: Advances in diagnosis and treatment, coupled with increased social status of people with disabilities, make society's responses to termination of pregnancy for fetal anomaly (TOPFA) more contentious. This study aims to understand medical and social care professionals' perspectives on the meanings and implications of non-lethal disability from birth, and to evaluate the relationship with perceptions of TOPFA. Methodology: Qualitative, in-depth interviews were conducted with 14 medical professionals and 9 social care professionals. The data were analysed using a generative thematic approach. Results: For social care professionals, abnormal experience of life had become the norm; their narratives of the consequences of fetal anomaly for family life were more nuanced, containing more detailed discussion of the complexities of living with a disabled person. In contrast, medical professionals' accounts of family life with an affected person were dominated by the consequences for the affected individual. The impact of predicted long term outcome in relation to decisions about TOPFA varied across both professional groups; at one end of the spectrum, some professional felt perceived risk was enough to support TOPFA; at the other extreme, individuals who had seen positive outcomes with a specific condition felt TOPFA was not acceptable. Conclusion: The professional groups discuss similar issues, but interpret them differently. Social care professionals focused on their professional insight into life with an affected person; this was used as a rationale for both accepting and not accepting TOPFA. Medical professionals focused on the perceived seriousness of the condition and the wording of the legislation.